2009
DOI: 10.1007/s00774-009-0127-x
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor necrotic factor agent promotes BMP-2-induced ectopic bone formation

Abstract: Etanercept (ETN), which is a recombinant human soluble tumor necrosis factor (TNF) receptor that inhibits TNF activity, is effective in the treatment of rheumatoid arthritis. We investigated the effect of ETN on recombinant human bone morphogenetic protein-2 (rhBMP-2)-induced ectopic bone formation in vivo. A block copolymer composed of poly-D,L-lactic acid with random insertion of p-dioxanone and polyethylene glycol (PLA-DX-PEG polymer) was used as the delivery system. Polymer discs (6 mm, 30 mg) containing 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…An accepted paradigm of HO formation includes three key components: multipotent progenitor cells capable of forming bone, a permissive niche, and an inciting inflammatory incident [6][7][8]. The majority of current literature supports a role for MSCs in modulating HO [9][10][11][12]. This is further confirmed by the fact that we observe trauma-induced HO to occur through an endochondral ossification process.…”
Section: Introductionsupporting
confidence: 70%
“…An accepted paradigm of HO formation includes three key components: multipotent progenitor cells capable of forming bone, a permissive niche, and an inciting inflammatory incident [6][7][8]. The majority of current literature supports a role for MSCs in modulating HO [9][10][11][12]. This is further confirmed by the fact that we observe trauma-induced HO to occur through an endochondral ossification process.…”
Section: Introductionsupporting
confidence: 70%
“…It has been reported that TNF-α impaired BMP-2-induced ectopic bone formation in mice, and treatment with anti-TNF-α agents maintained bone mass and protected against bone loss caused by TNF-α [13]. To demonstrate the relationship between PGRN and TNF-α in BMP-2 mediated bone formation, an ectopic bone formation model was created in the calf muscle of WT and human TNF-α transgenic (TNF-Tg) mice.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that overexpression of TNF-α enhances bone resorption and inhibits osteogenesis induced by BMP-2 [13]. TNFR1 is known to mediate inflammatory function of TNF-α, which also induces inflammatory bone resorption [14].…”
Section: Introductionmentioning
confidence: 99%
“…The burst release of growth factors is, additionally, considered unfavorable from the point of view of optimal bone regeneration, as their controlled and prolonged release is of vital importance to make the material osteoinductive 182,183 . Also, tumorigenesis, ectopic expression and other forms of ill-directed growth resulting from the uncontrolled dosage or location of delivered BMPs and other growth factors, including platelet-derived growth factor-BB, and present serious potential problems pertaining to their usage 184,185,186,187 . Strictly speaking, with the healing process following injury that the implantation of a hard tissue substitute is consisting of multiple steps, including clotting, angiogenesis, inflammation, scar formation, etc., each one of which occurs at a narrowly defined time scale, it makes sense that regulatory molecules targeting these specific events should be released within similarly narrowly defined time windows.…”
Section: Additional Common Ingredients Of Composite Biomaterialsmentioning
confidence: 99%